The effects of resistance training on jumping and selected power variables of the lower limbs in female soccer players - Chamera, T.; Pronczuk, M.; Smok, P.; Drozd, M.; Michalczyk, M.; Maszczyk, A. (Baltic Journal of Health and Physical Activity, 2023)
The aim of the study was to compare the effects of a 6-week intervention of combined soccer training with resistance training on strength and power variables in highly trained female soccer players. It was hypothesized that 6 weeks is sufficient for a significant improvement in jumping ability and power to occur due to the intervention. The study involved 34 female soccer players of the top women`s league (22 ± 5 years old, body height 167 ± 5 cm, body weight 60 ± 8 kg). The players were divided into two groups of 17 participants. The control group performed 3 soccer and 1 strength training sessions (50-60% 1RM load) weekly. The experimental group performed 3 soccer and 2 resistance training sessions during a weekly micro-cycle (50-85% 1RM load). The results of the experiment indicate a significant improvement in vertical jump height and sitting leg press performance in the experimental group: CMJ (p < 0.05; p = 0.000029; ES:1.00;11%), CMJA (p < 0.05; p = 0.003; ES = 1.09;13%) and LP (p < 0.05; p = 0.027681; ES = 0.48;6%), while in the control group changes in results after completing the training program were statistically insignificant for CMJ (p > 0.05, p = 0.274000, ES:0.07,1%), CMJA (p > 0.05, p = 0.350958, ES = 0.27;3%) and LP (p > 0, 05; p = 0.130153; ES = 0.27;4%). The presented results suggest that a short, six-week resistance training program, specific soccer training and strength training carried out twice a week during the preparatory period may significantly improve the strength and jumping variables of the lower limbs in female soccer players.